GE_GERICHTE C/10238/2012 vom 26. April 2013 - GE Cour de justice (2013)
EXÉCUTION(PROCÉDURE); DÉCISION ÉTRANGÈRE; RÉCIPROCITÉ(RAPPORT INTERNATIONAL); DROIT D'ÊTRE ENTENDU | LDIP.167.1; LDIP.29.2; LDIP.16; LDIP.166.1; Cst.29